ICE GRADING EQUIPMENT - DEVELOPMENT OF AN EXPERIMENTAL ROTATING-DRUM CUTTER - Gifford, S. E. (1964)
Tests of an experimental rotating-drum ice cutter are described. The tests were perf rmed to determine the feasibility of grading polar ice surfaces through removing excess ice by fracture, using impact cutters mounted on a rotating-drum. Experiments were conducted to learn the best shape, size, and number of cutters required; horsepower needed for various depths of cut and travel speeds; the relative merits of overcutting and undercutting; and the most suitable cutting-drum rotating speed. The ice cutter's performance, which was tested in a cold chamber, in Alaska, and in Greenland, revealed that removal of ice by fracture was feasible. The criteria obtained from these tests have been used to develop an ice dozer for pioneering in rough ice areas. This unit is currently being tested and evaluated at various field sites. (Author)